Stress and coping strategies among parents of children with attention deficit hyperactivity disorder - Bayle, Ma. Alona Chiu (2007)
Parenting children with special needs is stressful because of the additional demands and challenges of raising children with ADHD. This study focuses on the experiences of 42 parent respondents, particularly on their stress levels and coping strategies in raising children with ADHD. Using quantitative and qualitative data, the study surveyed the core symptoms of ADHD manifested by the respondents' children and identified the coping strategies that the parents employ to manage the stress. It was shown that the stress experienced by parents stems from symptoms associated with disruptive behaviors. The parents are generally aware about ADHD. They believe that SPED is an avenue for their children to learn.